Information Hiding 14th International Conference, IH 2012, Berkeley, CA, USA, May 15-18, 2012, Revised Selected Papers - Kirchner, Matthias; Ghosal, Dipak; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains the thoroughly refereed post-conference proceedings of the 14th Information Hiding Conference, IH 2012, held in Berkeley, CA, USA, in May 2012. The 18 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on multimedia forensics and counter-forensics, steganalysis, data hiding in unusual content, steganography, covert channels, anonymity and privacy, watermarking, and fingerprinting.
Multimedia Forensics and Counter-Forensics -- Blind Median Filtering Detection Using Statistics in Difference Domain -- Robustness of Color Interpolation Identification against Anti-forensic Operations -- Steganalyis -- Steganalysis of LSB Replacement Using Parity-Aware Features -- Statistical Detection of LSB Matching Using Hypothesis Testing Theory -- Textural Features for Steganalysis -- JPEG-Compatibility Steganalysis Using Block-Histogram of Recompression Artifacts -- Data Hiding in Unusual Content Hiding a Second Appearance in a Physical Relief Surface -- Blind Robust Watermarking Mechanism Based on Maxima Curvature of 3D Motion Data -- Steganography A Game-Theoretic Approach to Content-Adaptive Steganography -- Key-Efficient Steganography -- Covert Channels Secret Agent Radio: Covert Communication through Dirty Constellations -- Anonymity and Privacy Lower Bounds for Private Broadcast Encryption -- The Dangers of Composing Anonymous Channels -- Watermarking A New Measure of Watermarking Security Applied on QIM -- Non-Integer Expansion Embedding for Prediction-Based Reversible Watermarking -- Walsh-Hadamard Transform in the Homomorphic Encrypted Domain and Its Application in Image Watermarking -- Fingerprinting Asymptotic Fingerprinting Capacity in the Combined Digit Model -- Bias Equalizer for Binary Probabilistic Fingerprinting Codes.
Keywords: Computer science; Data encryption (Computer science).; Computer software; Multimedia systems; Computer graphics; Computer vision; Information Systems; Computer Science; Data Encryption; Algorithm Analysis and Problem Complexity; Multimedia Information Systems; Management of Computing and Information Systems; Image Processing and Computer Vision; Computer Graphics